SEMANTICS OF TRAVEL AND DISCUSSIONS ON GENESIS (Scientific journal of the Fergana State University, 2023)
Travel motifs dominate folklore epics, especially fairy tales and epics. The purpose of this study is to study the views of folklore on the genesis and semantics of the motive of the trip in a comparative-typological method. The results of the research show that the genesis of the motive of the journey is connected with the first period of humanity, and as a result of the development of society, the semantic scope of the journey has expanded according to the purpose and direction. The main conclusion of the study is that the transformation of the reality of life in the process of its transformation into an artistic reality led to the depiction of this motif as a stage of heroic maturity and formation.